(untitled) (Modern information system and technologies, 2018)
The article deals with cryptography in general and the need for transition to post-quantum cryptography. The purpose of the work is to study a new and interesting trend in cryptography, namely, post-quantum cryptography. The stability of cryptosystems based on the task of discrete logarithm to attacks by intruders on classified data is analyzed. Also, methods of using isogenesis for construction of cryptosystems are considered.